Effect of surfactant on functionalized multi-walled carbon nano tubes enhanced salt hydrate phase change material - Kumar R, Reji; A.K., Pandey; Samykano, Mahendran; Nath Mishra, Yogeshwar; R.V. Mohan, R.V.; Sharma, Kamal; Tyagi, V.V. (Elsevier, 2022)
Phase change materials (PCMs) are effective thermal energy storage materials; however, their low thermal conductivity nature tends to affect heat storage performance. Salt hydrate being inexpensive, incombustible and ensuring high phase change enthalpy, are highly attractive for energy storage. The potential of multi-walled carbon nanotubes (MWCNTs) in improving the thermophysical properties of salt hydrate PCMs makes it a hotspot of current research. Therefore, in this research article, MWCNTs and functionalized multi-walled carbon nanotubes (FMWCNTs) nanoparticles were dispersed with inorganic salt hydrate at different concentrations (0.3, 0.5, and 1.0 wt%), in the presence and absence of surfactant. The role of surfactant with salt hydrate PCM has been discussed extensively. The results obtained have ensured an enhancement in melting enthalpy of prepared composites by 4.92 %, and 28.5 % for 0.5 wt% MWCNT dispersed PCM (SHM0.5), and 0.5 wt% FMWCNT dispersed PCM (SHF0.5), respectively. Furthermore, the maximum thermal conductivity was enhanced by 50.0 % and 84.78 % for 0.5 wt% MWCNT dispersed PCM with surfactant (SHMS0.5), and SHF0.5 respectively, compared to salt hydrate PCM. From the improvement in thermal conductivity, light absorptance, thermal stability, latent heat, and chemical stability, it is evident that the prepared nanocomposite is a potential candidate for solar thermal energy storage application